PENGENDALIAN EMOSI KARYAWAN DALAM BIDANG JASA (CAFE) - Dian Yudhawati & Sinta Mayasari (LPPM Universitas Proklamasi 45, 2015)
Emotional labor is employee's ability to manage affect, and therefore his or her physiognomy and physical gesture are publicly accepted. Emotional labor requires employee to show pleasant behavior, such as smiling, and suppress the negative affect especially when serving consumers. Indeed, it is very difficult since consumer in service industry behaves haphazardly. Objective of this preliminary is to discuss employee’s emotional labor situation. A cafe employee participates in this qualitative research. He is asked to be a research subject since his personal manager reported of frequent laziness when serving consumers. This research revealed that the subject has considerable work experiences. Unfortunately, he has less ability to manage his emotion when serving consumers. He is more likely to adapt surface acting than deep acting in order to manage his emotion.